The Effect of Treating String Bean Pods with Modified Atmosphere Packaging and UV-C Irradiation on Their Storage Life - Jolanta Franczuk (Agronomy, 2021)
The aim of the experiment was to determine the optimal treatment of string bean pods, prolonging their storage life. To this end, the effect of modified atmosphere packaging in Xtend® bags (CH-49) and UV-C radiation on the quality of string beans ‘Unidor’ in cold storage was studied. Observations of the pods and their measurements were made after 14 and 28 days and chemical analyses 14 days after irradiation exposure and storage at 2–4 °C. The tests were conducted in laboratory conditions in a completely randomized design. Storing bean pods in Xtend® bags significantly increased the weight and umber of pods fit for consumption, compared to those stored in bulk. However, the content of dry matter, total sugars, and protein in pods stored in Xtend® bags decreased. Irradiation, regardless of the exposure time and the distance of lamps from the surface, contributed to an increase in the weight and number of pods suitable for consumption after 14 and 28 days. After 14 days irradiated pods contained more dry matter, L-ascorbic acid, polyphenols and flavonoids. After UV-C irradiation for 600 s with lamps at a height of 40 cm pods in Xtend® bags responded with the most favorable protein content.